Buprenorphine and norbuprenorphine findings in hair during constant maintenance dosage - Skopp, Gisela; Kniest, Anja; Haißer, Jörg; Mann, Karl; Hermann, Derik (International journal of legal medicine, 2011)
It is still a matter of debate whether a positive correlation between the dose and the amount of drug in the hair exists. Drugs such as buprenorphine (BUP) used under controlled conditions present an opportunity to prove a possible relationship. Due to discrepant findings of BUP/norbuprenorphine (NBUP) ratios in hair, in vitro degradation of both analytes in diluted acid was also investigated. The levels of BUP and NBUP in proximal hair sections from 18 subjects participating in a maintenance program were determined by liquid chromatography/tandem mass spectrometry following incubation with methanol and subsequent liquid/liquid extraction. BUP and NBUP were incubated in diluted hydrochloric acid at 60°C for up to 24 h. The alleged rearrangement products were simultaneously monitored. All hair samples tested positive for BUP (lower limit of detection-0.238 ng/mg hair) and NBUP (0.043-0.961 ng/mg hair). The concentration of NBUP in hair was consistently higher than that of BUP except for a single specimen. Degradation of BUP and NBUP was dependent on time; hydrolysis of NBUP occurred faster than that of BUP. The concentration of BUP and NBUP will be underestimated if analytes are recovered by acidic procedures. NBUP should be monitored in hair samples besides BUP for the sum of both BUP and NBUP may provide an estimate of BUP exposure following long-term administration of the drug.
Gesehen am 18.10.2022